Coarse particles and hospital admissions due to respiratory diseases in children. An ecological time series study - César, Ana Cristina Gobbo (2018)
BACKGROUND: Exposure to particulate matter (PM) is associated with hospitalizations due to respiratory diseases among children. DESIGN AND SETTING: An ecological time series study was carried out to identify the role of coarse fractions of particulate matter (PM10-2.5) in hospitalizations among children up to 10 years of age, in Piracicaba (SP) in the year 2015. METHODS: A generalized additive model of Poisson regression was used to estimate the risk of hospitalization due to acute laryngitis and tracheitis, pneumonia, bronchitis, bronchiolitis and asthma. Lags of 0 to 7 days were considered, and the model was adjusted for the temperature and relative humidity of the air and controlled for short and long-term exposure. Proportional attributable ratios, population-attributable fractions and hospital costs were calculated with increasing concentrations of these pollutants. RESULTS: 638 hospitalizations were evaluated during this period, with a mean of 1.75 cases per day (standard deviation, SD = 1.86). The daily averages were 22.45 μg/m3 (SD = 13.25) for the coarse fraction (PM10-2.5) and 13.32 μg/m3 (SD = 6.38) for the fine fraction. Significant risks of PM10-2.5 exposure were only observed at lag 0, with relative risk (RR) = 1.012, and at lag 6, with RR = 1.011. An increase of 5 μg/m3 in the coarse fraction concentration implied an increase in the relative risk of hospitalizations of up to 4.8%, with an excess of 72 hospitalizations and excess expenditure of US$ 17,000 per year. CONCLUSIONS: This study showed the impact of coarse-fraction exposure on hospital admissions among children due to respiratory diseases.